KEPADATAN, KEANEKARAGAMAN DAN POLA DISTRIBUSI GASTROPODA DI DANAU DIATAS, KABUPATEN SOLOK, PROVINSI SUMATERA BARAT - Sindi Mardatila; Izmiarti Izmiarti; Jabang Nurdin (Biology Department, Mathematics and natural science, Tadulako University, 2016)
The study about Diversity and Distribution Patterns of Gastropods On Littorall Zones in Lake Diatas, Solok regency, West Sumatra, had been conducted from April to June 2015. Purposes of this study are to determine the diversity and distributeon patterns of gastropods in the littoral zone of the Lake Diatas. This research was conducted using a survey methods and gastropods sampling with purposive sampling. Six stations were chosen as sampling location with 1-1.5 meters depth using squared plot size of 60 x 60 cm2 and divided into 4 sub-plots. The result showed diversity index of gastropods of over all population in the lake above1,21 and population density of 284,17ind/m2. The highest index value diversity of gastropods populations found in station Villa is 1.70 and the lowest was found in Gelagah station 0,67. The total value of the highest population densities gastropods found in Gelagah station which is 518,33 ind/m2, and the lowest density at the Villa station is 142,78 ind/m2. The distribution pattern in the Lake Diatas of gastropods are clustered, whereasthe distribution pattern at each station varies from uniform and clumped. Factorsc hemical and physic swater conditions at Lake Diatas still support life of Gastropods and density is very influenced by the substrate. Keyword: Gastropod, Diversity, Density, Distribution Pattern,Littoral zone.